POLA PENGELUARAN DAN GAYA HIDUP PENDUDUK MUDA KELAS MENENGAH: STUDI EMPIRIS PERKOTAAN DI JABODETABEK (EXPENDITURE PATTERN AND LIFESTYLE OF YOUNG MIDDLE CLASS POPULATION: EMPIRICAL STUDY FROM URBAN CITIES OF GREATER JAKARTA) - Vanda Ningrum; Intan Adhi Perdana Putri; Andini Desita Ekaputri (Research Centre for Population, Indonesian Institute of Sciences, 2014)
Youth occupies a great segment of population in metropolitan cities. Since the era of industrialization in 1980s, many of these youth are categorised asÂ middle class group. Their expenditure patterns and lifestyle have a strong influence to the country economics as well as urban planning regulations. This paper aims to analyse the behaviour of youth who perceived themselves as young middle class population based on their expenditure pattern and lifestyle. The research surveyed those whose age spans from 18 to 35 years old, reside and work in theurban cities, namely Jakarta, Bogor, Depok, Tangerang, and Bekasi. Results of the survey showed, there is a different pattern of consumption betweenÂ young middle class population who are single and married. Single individuals tend to spend their monthly income for food culinary as their first priority. In the other hand, young marriage couple tends to spend their income for paying their house or car loans. Although, in average, young middle class frequently visit shopping malls, their expenditure on entertainment is not their top priority from total expenditure per month. Their main reason visiting malls is to seek for a convenient environment compared to spending their income as a mean to reach a certain social status. Given the imbalance between growing number of malls (supply) and lack of spending (demand), moratorium of malls can be one regulations issued by the government to providea lternative public areas or Open Green Areas (RTH) such as parks.